Fostering Innovation: HR Practices and Knowledge Sharing with the Mediating Effect of Knowledge Management Success and the Moderating Role of Innovation Culture (Journal of Asian Development Studies, 2025)
This study examines the relationship between human resource (HR) practices, knowledge sharing, and organizational innovation, with a focus on the mediating role of knowledge management (KM) success and the moderating effect of innovation culture. A quantitative approach was utilized, surveying professionals from diverse sectors in Karachi, Pakistan. The data were analyzed using Structural Equation Modeling (SEM) to test direct, mediating, and moderating effects. Results indicate that HR practices significantly enhance KM success, which in turn facilitates knowledge sharing, innovation’s key driver. Innovation culture strengthens the relationship between KM success and knowledge sharing, highlighting the importance of an organizational culture that promotes creativity and collaboration. This study contributes to existing literature by confirming the critical roles of HR practices and KM success in fostering knowledge sharing and innovation across various industries. Practical implications suggest that organizations aiming for sustainable innovation should invest in HR practices that support KM and cultivate a culture of innovation.